Systematic integration in the study and understanding of social phenomena – An Analytical Study of Social Research Methods and Methods – - Alkasem, Mayada Mustafa (Journal of Humanities & Social Sciences, 2021)
The aim of the research is to clarify the method of systematic integration in the study of social phenomena, which is considered one of the most important methodological cognitive issues in curriculum science, through the use of the qualitative and quantitative method in the study of one social phenomenon. This study aimed to achieve synergy and systematic integration between the various social research methods. In order to increase the understanding of the studied phenomena as well as to reach better results in the field of social research to enrich scientific and social knowledge. This study also came to clarify the importance of the integration of the quantitative and qualitative approaches in the study of social phenomena due to their contribution to deepening the understanding and interpretation of the social phenomena addressed to the study and research. The study also sought to clarify the methodological approaches, approaches and methodological tools that together constitute an integrated unit represented in the systematic construction of sociology, as well as It aimed to define the basic dimensions of methodological integration, and the research relied on the analytical sociological approach as an approach and method for analysis in the field of social studies, and the study concluded that relying on the quantitative approach only in the study of social phenomena does not lead the researcher to accurate and honest results, just as the use of the qualitative approach is not sufficient. To treat social phenomena, they must be used together to better and stronger support for interpretation. The study also found the extent of the importance of multiple approaches to the study of one social phenomenon. The research also recommended a set of recommendations, the most important of which are: Calling researchers to use methodological integration in studying social phenomena, linking theory with social reality, and the necessity to use at least one form of methodological integration in one study.